2016
DOI: 10.5527/wjn.v5.i2.125
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles as mediators of vascular inflammation in kidney disease

Abstract: Vascular inflammation is a common cause of renal impairment and a major cause of morbidity and mortality of patients with kidney disease. Current studies consistently show an increase of extracellular vesicles (EVs) in acute vasculitis and in patients with atherosclerosis. Recent research has elucidated mechanisms that mediate vascular wall leukocyte accumulation and differentiation. This review addresses the role of EVs in this process. Part one of this review addresses functional roles of EVs in renal vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 190 publications
(194 reference statements)
0
20
0
Order By: Relevance
“…EVs are produced constitutively or upon activation, due to inflammation, hypoxia, oxidative stress, shear stress, senescence, cell death, exposure to bacterial endo/exotoxins, uremia, etc. [10][11][12][13][14][15]. The cargo varies depending on type and differentiation of the parent cell, microenvironmental variables, and agents that triggers EV release.…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…EVs are produced constitutively or upon activation, due to inflammation, hypoxia, oxidative stress, shear stress, senescence, cell death, exposure to bacterial endo/exotoxins, uremia, etc. [10][11][12][13][14][15]. The cargo varies depending on type and differentiation of the parent cell, microenvironmental variables, and agents that triggers EV release.…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…It has been observed that EVs can be released during physiological events in vivo, such as cell growth, proliferation, activation, apoptosis, or senescence. Furthermore, some conditions, such as oxidative or shear stress, inflammation, senescence, and cell death, may also induce EV production [13][14][15][16][17][18]. In any case, EVs are released into the extracellular milieu and finally they could reach the blood circulation.…”
Section: Extracellular Vesicles Subtypesmentioning
confidence: 99%
“…EVs are highly heterogeneous structures that differ in size, biochemical content and mode of secretion. Current nomenclature distinguishes three populations of EVs: (1) exosomes (30ā€“100 nm), which originate when multivesicular bodies fuse with the plasma membrane, (2) microvesicles/ectosomes (100ā€“1,000 nm), which are generated by budding of the plasma membrane and (3) apoptotic bodies (>1,000 nm), which are formed in the process of programmed cell death ( 2 ā€“ 5 ). Each family is composed of small phospholipid membrane-enclosed entities released spontaneously, or, in response to cell activation or apoptosis ( 6 ).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%